2017
DOI: 10.21608/adjg.2017.5289
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Smile Characteristics in Different Dentoalveolar Malocclusion Cases

Abstract: Objectives: This study was designed to assess the smile characteristics in different dentoalveolar malocclusion cases, by standardized photographic analysis. Subjects and methods: A sample of 132 subjects with age range from 18 to 24 years. The study groups were designed according to Angles Classification in to 4 groups. Standardized extraoral photographs at rest position, social smile, maximum smile and profile were taken for each subject. Smile analysis was done by identifying certain measurements digitally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…While the lowest values when smiling were observed in subjects with class II malocclusion. These results were consistent with other studies showing that class III subjects had the highest lower lip height values [29], [30], and [31]. Reduced height of the lower third of the face is associated with a vertical maxillary deficit and a deep bite with retrognathism of the mandible.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While the lowest values when smiling were observed in subjects with class II malocclusion. These results were consistent with other studies showing that class III subjects had the highest lower lip height values [29], [30], and [31]. Reduced height of the lower third of the face is associated with a vertical maxillary deficit and a deep bite with retrognathism of the mandible.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, the largest vertical display of upper central incisors was observed during social smile in untreated and treated individuals with class I malocclusion, which is consistent with the study by Abdarazik et al and the smallest in class III malocclusion [29]. In the study by Salehi et al a significantly greater display of central incisors was observed in patients with class II malocclusion compared to those with class III malocclusion [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To achieve uniformity of shape in orthodontic treatments, it is necessary to assess the inherent features of the smile. This requires identifying the elements and circumstances that influence these traits [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous writers have distinguished between various sorts of smiles; one writer distinguished between two fundamental forms of smiles: Put on a grin (the social grin): it's a deliberate, relaxed, motionless facial expression with only mildly contracted muscles. This is the smile that people usually use to say hello [ 3 ]. A person who consistently and voluntarily smiles in social situations is said to be wearing a social smile.…”
Section: Introductionmentioning
confidence: 99%